Animating Instructional Materials in Computer Education: An Approach to Designing and Teaching Concepts in Data Structures Using LATEX - Damilola Osikoya; Adeleke Oluwalani (European Alliance for Innovation (EAI), 2012)
Animation gives a different perception on what is being visually presented. Research has shown that students are likely to understand what is being taught from the combination of animation and text than just with text. Students easily understand scientific concepts in narrative and animated forms. Data structure is a way of storing and arranging data. The efficacy of searching these stored data is very important, so is it vital that they are stored with the right algorithm. This paper presents animations designed to support teaching in computer education. Our main focus is to present controlled animated instructional materials in teaching topics in data structures. We have created three scientifically animated instructional materials in data structures consisting of the Stacks, Queues and Trees. These scientific spheres have been chosen to demonstrate the basic ideas of this work, because of its simplicity in representing the animations. We hope to develop reasonable sets of instructional material of different subject areas that will be stored in a database repository. These are intended to be delivered to students through an e-learning website and/or Mobile phones to support them with additional learning opportunities.